A Patient With Plaque Type Morphea Mimicking Systemic Lupus Erythematosus - Wardhana Wardhana; EA Datau (Acta Medica Indonesiana)
Morphea is an uncommon connective tissue disease with the most prominent feature being thickening or fibrosis of the dermal without internal organ involvement. It is also known as a part of localized scleroderma. Based on clinical presentation and depth of tissue involvement, morphea is classified into several forms, and about two thirds of adults with morphea have plaque type. Overproduction of collagen production by fibroblast is the cause of abnormality in morphea, and the hyperactivity mechanism of fibroblast is still unknown, although there are several mechanisms already proposed. Plaque type morphea is actually a benign and self limited. Plaque type morphea that mimicking systemic lupus erythematosus in clinical appearance, such as alopecia and oral mucosal ulcers, is uncommon. A case of plaque type morphea mimicking systemic lupus erythematosus in a 20 year old woman was discussed. The patient was treated with local and systemic immunosuppressant and antioxydant. The patient’s condition is improved without any significant side effects.